2020
DOI: 10.1002/lno.11638
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized autonomous sampling reveals coupled pulses of biomass and export of morphologically different diatoms in the Southern Ocean

Abstract: The Southern Ocean hosts a large diversity of diatoms that play a major role in carbon fluxes. How the seasonal dynamics in the abundance of specific taxa in surface waters are linked to their contribution to carbon export remains, however, poorly understood. We present here synchronized observations from autonomous samplers deployed in the mixed layer (42 m) and at depth (300 m) during an entire productive season (October 2016 to March 2017) in the iron fertilized region of the central plateau of Kerguelen. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 54 publications
7
24
0
Order By: Relevance
“…Another diatom abundant in Austral summer in the study region is Rhizosolenia spp. (Armand et al, 2008;Blain et al, 2020;Lafond et al, 2020). This diatom revealed strong positive correlations with the Roseobacter genus Loktanella (Liu et al, 2020), a taxon that was highly abundant in off-plateau waters in the particle-attached fraction in the present study.…”
Section: Potential Role Of Biotic Interactions In Shaping Community Compositionsupporting
confidence: 54%
See 1 more Smart Citation
“…Another diatom abundant in Austral summer in the study region is Rhizosolenia spp. (Armand et al, 2008;Blain et al, 2020;Lafond et al, 2020). This diatom revealed strong positive correlations with the Roseobacter genus Loktanella (Liu et al, 2020), a taxon that was highly abundant in off-plateau waters in the particle-attached fraction in the present study.…”
Section: Potential Role Of Biotic Interactions In Shaping Community Compositionsupporting
confidence: 54%
“…Prokaryotes contribute substantially to the transformation of phytoplankton-derived organic matter during early spring (November), summer (January-February) and late summer (February-March) corresponding to the onset, peak and early decline, and the post-bloom phases in these perennially cold waters (Christaki et al, 2020). These diatom-dominated blooms (Armand et al, 2008;Lasbleiz et al, 2016;Blain et al, 2020) are associated with prokaryotic heterotrophic communities during early spring (Landa et al, 2016) and in summer (West et al, 2008;Obernosterer et al, 2011) that are distinct to those in surrounding low-productive waters. Onboard experiments have highlighted the role of diatom-derived organic matter in shaping prokaryotic community composition in spring (Landa et al, 2016), and potential associations between diatom species and prokaryotic taxa has been identified as mechanism for the temporal structuring of microbial communities (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Their disapperance 8 hours later further suggests an export event in the form of loose aggregates, that were not cohesive enough to stay aggregated below the surface layer. This observation could reconcile our data showing mostly single cells in the the intermediate layers, with the mecanism of rapid export proposed by Blain et al (2020), which would lead to a rapid flushing of the surface layer of diatoms in the form of aggregates, once reached a critical cell concentration and stickiness threshold value. In another study carried out in the Antarctic Zone, sediment trap data results suggested a fast and undisturbed transport of particles between 2000 and 3700, and sinking velocities of 210 m -2 d -1 of the major diatom taxa were estimated (Rigual-Hernández et al, 2015).…”
Section: Nature Of the Deep Particle Stocksupporting
confidence: 90%
“…The similarity of the taxonomic diatom composition in the Bottle nets compared to the above surface layer phytonets (Fig. 6) furthermore suggests a rapid export mode of diatoms, which has already been hypothesized in the same region with observations of similar taxonomic composition between the surface layer and sediment taps moored at 300 m (Blain et al, 2020). We therefore hypothesize that these cells sank rapidly out of the surface layer, included in loose phytodetritus or aggregates which disaggregated in situ prior to collection, due to shear stress in the water column or to bacterial mineralization of TEP/colloids holding aggregates together.…”
Section: Nature Of the Deep Particle Stocksupporting
confidence: 74%
“…It is likely that lower surface biomass during the 2017-18 bloom (Fig. 2a) led to lower levels of aggregation 33 , as evidenced by the lower peak mean particle size (Fig. 2c).…”
Section: Seasonality Of Multiple Carbon Export Pathwaysmentioning
confidence: 99%